The construction and validation of solution-focused group work (SFGW) for Malaysian adolescents - Shunmugam, Ratnadevi R; Noah, Sidek Mohd (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2017)
Solution-focused Group Work (SFGW) approach is proven to be effective in resolving adolescents’ life struggles and assist them to lead a successful adolescence hood. Common practices of developing the intervention module and assessing the module are presented in this study. The data was collected by two stages: (i) validation process by 4 counseling module development experts; and (ii) a total of 30 samples aged 14-15 years old was piloted to obtain the reliability score of SFGW. The collected data were subjected to descriptive test. The result yielded that SFGW have good validity and high reliability with Cronbach’s alpha of .87 and .94 respectively. Hence, it is concluded that SFGW is a valid and reliable module for adolescents who increases their self-efficacy, achievement motivation and goal-setting behaviors.